(untitled) (Research, Society and Development, 2021)
The Physical Education professional in essence plans, elaborates, organizes, builds, executes and structures models and training sections, masters concepts and procedures related to the body, health and physical activity. In preparing the training program, it takes into account aspects related to the individuality of the student / client, socioeconomic factors, health in general, objective and purpose with the practice of the activity. In the act and exercise of his profession, he applies intellectual property, and in the construction of his product he presents criteria and characteristics related to copyright. There are characterizing elements in CONFEF Resolution No. 327/2016 that corroborate the criteria of LAW No. 9,609 / 98 of copyright in Brazil. Based on this premise, this article aimed to identify whether, in the exercise of their profession, the Physical Education professional develops a passive product of copyright protection, as well as to know the characteristics and criteria in the prescription of physical activity. While problematic, it is worth noting whether the Physical Education professional builds a product and if that product fits the protection of copyright. In the methodological field, principles of documentary research were used, analyzing and comparing CONFEF Resolution No. 327/2016 and LAW No. 9.609 / 98. Obtaining the following information, there is a relationship between training programs and copyright protection; the Physical Education professional demands passive action for discussion in the face of copyright protection; there is a need to deepen the discussion regarding the prescription of physical activity, physical education professional and copyright.